Oil Crisis in the Niger Delta Region of Nigeria: Genesis and Extent - Tombari Bodo; Batombari Gbidum Gimah (European Scientific Journal, ESJ, 2019)
The people of Niger Delta have suffered several years of negligence and marginalism from the exploration of petroleum and distribution of its products by multinational oil companies and the government. This has necessitated attacks from the locals on government forces, oil workers, and oil installation sites as a means of expressing their grievances. The oil crisis in the region has led to the disruption of oil exploration and reduction of revenues accruing to the state from the sales of oil. These crises have led to the multiplication of several criminal vices that has turned the region into a state of disarray. The military and the militants are currently benefiting from the booming business of illegal bunkering, pipeline vandalism, and diversion of refined petroleum products running through the pipes from the refineries. This paper focuses on examining the history of oil exploration, origin, and consequences of the oil crisis in the Niger Delta, and how the government can put an end to this menace.